Die Entzauberung des Westens in Julia Francks Roman Lagerfeuer - Jaśkiewicz, Grzegorz (Tematy i Konteksty, 2017)
This text is devoted to the phenomenon of realism in postwar German novel on the example of the younger generation author Julia Franck (Born 1970). The tradition of realistic writing in German literature reaches the first half of the 19th century when mainly Georg Büchner postulated and realized realistic art. Consecutive authors, the great realists of the 19th century like Theodor Fontane saw in realism not only the reflection of reality in literature but embellishing it. After World War II great German writers like Böll, Andersch, Koeppen or Walser recalled Western Germany with its society in their realistic novels. Their characteristic feature was objectively marked narration. And Franck’s novel is this way as well. Told from the perspective of four people it shows what was „talked about”. Repatriation or escape to the West did not mean entering paradise. Runaways still experience humiliation, have to deal with the environment and themselves. The esthetic category is ugliness. And from this perspective the lives of heroes/narrators are analyzed.